Localization of eukaryotic initiation factor 3 on native small ribosomal subunits - Emanuilov, Ivan (1978)
The localization of eukaryotic initiation factor 3(eIF-3) on native small ribosomal subunits has been established by electron microscopy through a comparison of native small ribosomal subunits with derived subunits and with native subunits stripped of eIF-3. Small subunits derived from reticulocyte ribosomes by the puromycin/KCl method are seen in electron micrographs as elongated particles, divided by a heavily stained partition into approximately one-third and two-third domains. Most particles (60-70%) observed in electron micrographs of native small subunit preparations resemble derived small subunits, but have an additional mass attached to one side, thus producing profiles with a three-lobed appearance. The mass measures approximately 160 × 100 × 60 Å, and its particle weight is estimated to be about one-third to one-half that of a 40S subunit. The site of attachment of the additional mass is located on a prominence extending from the central part of the small subunit and is separated by a cleft from the smaller third of the subunit. The remaining particles in preparations of native subunits resemble the profiles seen in electron micrographs of derived subunits. After removal of eIF-3 by treatment with high concentrations of salt, profiles observed in electron micrographs of washed, native subunits were indistinguishable from those of derived subunits. Since removal of eIF-3 coincided with removal of a mass of the correct molecular weight, subunits with the three-lobed appearance are identified as native small subunits carrying eIF-3.